The problematic of the jurisdiction of the Court of Arbitration for Sport (CAS) in the consideration of national disputes for players football contract (Damascus University Journal for legal sciences, 2025)
The Court of Arbitration for Sport plays a leading role in the field of settling sports disputes, the jurisdiction of the court extends to various kinds of sports disputes. In the field of football, we find that the International Federation of Football Associations "FIFA" has recognized the Court of Arbitration for Sport as a judicial body competent to consider disputes to which it is a party. But is the court competent to consider national disputes that arise between players and clubs at the national level, and can parties at the national level resort to this court? In this research, we will review the possibility of relying on Article /56/ of the FIFA regulations to grant the court jurisdiction to consider national disputes, and then we will search for the legal basis on which to grant the Court of Arbitration for Sport this jurisdiction, in light of the jurisprudence of this court.
Keywords: Court Of Arbitration For Sport; FIFA Regulations; Players Contract; National Disputes; Jurisdiction